Draft genome assembly and bioinformatic analysis of a denovo sequenced genome of Treponema phagedenis like strain V1 - Mushtaq, Mamoona (2012)
In this study, a draft genome assembly of Treponema phagedenis-like strain V1 was obtained using Mira3 assembler. T. phagedenis-like strain V1 was isolated and characterized from a digital dermatitis lesions, a skin disease causing lameness in cattle. The draft assembly of Mira consisted of 812 contigs with 105 contigs of length >10,000 bp and 707 contigs of length <10,000 bp. The total number of bases in all the contigs was 3560210 with an average GC content of 40.53%. The assembly obtained with Mira3 was of good quality, average consensus quality was 79 with average contig coverage 29.39. Annotation of the draft genome sequence using an in-house annotation pipeline predicted 3507 open reading frames (ORFs) of which, 1018 encode for proteins that have homologues in T. denticola and 382 ORFs encode for proteins having homologues in T. pallidum. Genes encoding for lipoproteins, hemolysins, proteases, lipases and different types of antigens were also predicted, these genes could be involved in the pathogenesis and virulence in T. phagedenis-like. Genome comparison of T. phagedenis-like with T. pallidum and T. denticola showed more similarity of the T. phagedenis-like genome with that of T. denticola than with T. pallidum. Scaffolding and finishing steps of the assembly will be performed further and complete annotation including the structural and functional annotation of all the genes and proteins will be performed, and interesting findings will be validated using molecular biology techniques.